Bury my heart at conference room B - Slap, Stan (Tantor Media, Inc., 2010)
The stories about Stan Slap are so remarkable that they seem like myths: He brought a room full of top-level Microsoft managers to tears, leaving them cheering "I'm hurting, too!" After a single speech at Patagonia, the company asked him to join its board of directors. One CEO described him as "Stephen Covey meets Nine Inch Nails." All this from a man who never graduated from business school, college, or even high school. Bury My Heart at Conference Room B harnesses the awe-inspiring insights of Slap's life-changing management workshops. The book is a powerful tool for creating emotional commitment in managers. That means unchecked, unvarnished devotion to the company. If you've ever witnessed a human being emotionally committed to a cause-working like they're being paid a million when they're not being paid a dime-you know that discretionary effort is worth more than their financial, intellectual, and physical commitment combined. Through unexpected case studies and a battle-tested self-assessment program, Slap shows how to help people live their deepest personal values at work, with huge payoffs for the companies that support their engagement.